(untitled) (Progressive Agriculture, 2018)
Source-sink manipulation may improve light interception into the canopy and reduce the competition between vegetative and reproductive sinks during seed filling period, and may help in achieving higher yield. So, an effort was made to assess the effect of source-sink manipulation on yield contributing characters and yield of sesame. The experiment was laid out in two factors randomized complete block design consisted of two varieties of sesame viz.Binatil-3 and Local-Black and five levels of source-sink manipulation viz.control (M0), removal of lower empty leaves, lower empty branches and top of the inflorescence (M1), removal of top of the inflorescence (M2), removal of all branches and removal of lower empty leaves (M3) and lower empty branches (M4) with three replications. Source-sink manipulations were imposed during capsule development stage (50 days after emergence). Results revealed that the higher number of capsules plant-1 (16.17), seeds capsule-1 (53.27), maximum 1000-seed weight (2.72 g), higher seed capsule wall ratio (2.52), seed yield plant-1 (2.35 g), yield (938.96 kg ha-1) and harvest index (36.40%) were produced by the modern variety Binatil-3 than the traditional variety Local-black. Source-sink manipulation showed positive response to yield attributes compared with control. Maximum seeds capsule-1 (57.13), 1000-seed weight (2.92 g), higher seed capsule wall ratio (2.71), seed yield plant-1 (2.78 g) and yield (1110.96 kg ha-1) were found from removal of lower empty leaves, lower empty branches and top of the inflorescence (M1). Yield was increased by 71.77%, 46.88%, 8.52% and 22.45% due to M1, M2, M3 andM4 manipulation. Although all the source-sink manipulation treatments gave higher yield in their respective variety, the highest (1258.63 kg ha-1 and 125.04%) yield was obtained when lower leaves, lower empty branches and top of the inflorescence of the variety Binatil-3 were removed i.e. from V1M1 treatment. Therefore, Binatil-3 with removal of lower empty leaves, lower empty branches and top of the inflorescence manipulation was the best treatment in respect of yield and yield contributing characters of sesame. Progressive Agriculture 29 (1): 1-9, 2018